Gut Barrier Dysfunction and Microbiota Variations in Cryptosporidiosis: A Comprehensive Review - Munwar Ali; Chang Xu; Mingyue Wang; Qazal Hina; Yaru Ji; Subiha Anwar; Sijia Lu; Qing He; Yawei Qiu; Kun Li (Veterinary Sciences)
Cryptosporidiosis is a zoonotic protozoan parasite-born disease, equally significant in both animals and humans, especially affecting immunocompromised individuals (e.g., AIDS patients) and neonates. The prime concerns of this review article are to demonstrate the disruption of the intestinal barrier and variations in the gut microbiome during cryptosporidiosis, and to explore host gut–parasite interactions that can lead to the development of novel therapeutics. The review concluded that the enteric barrier is particularly maintained by tight junction proteins (e.g., occludin, claudin, and ZO-1, etc.) and mucosal immunity, both of which are severely compromised during Cryptosporidium spp. infections, resulting in increased intestinal barrier permeability, inflammatory responses, diarrhea, and ultimately death in severe cases. Cryptosporidium-induced dysbiosis is characterized by reduced microbial diversity and richness, a shift from commensal to pathogenic bacteria, as evidenced by increased pro-inflammatory taxa like Proteobacteria, and reduced proportions of beneficial SCFAs producing bacteria, e.g., Firmicutes. Recent investigations have highlighted the interrelations between gut microbiota and epithelial barrier integrity, especially during cryptosporidiosis, demonstrating the modulations regarding tight junctions (TJs), immune reactions, and SCFA production, all of which are main players in alleviating this protozoal parasitic infection. This review comprehensively describes the fine details underlying these impairments, including autophagy-mediated TJs’ degradation, inflammasome activation, and gut microbiome-driven alterations in metabolic pathways, providing the latest relevant, and well-organized piece of knowledge regarding intestinal barrier alterations and microbial shifts during cryptosporidiosis. This work emphasizes the future need for longitudinal studies and advanced sequencing techniques to understand host gut microbiota–parasite interactions, aiming to formulate innovative strategies to mitigate cryptosporidiosis.